Info and Subscribes the SUSURGALUR Journal, Issue of March 2016 - SUSURGALUR, Editor Journal (SUSURGALUR, 2016)
SUSURGALUR journal will provide a peer-reviewed forum for the publication of thought-leadership articles, briefings, discussion, applied research, case and comparative studies, expert comment and analysis on the key issues surrounding the history education and historical studies in general and its various aspects. Analysis will be practical and rigorous in nature. The SUSURGALUR journal, with Print ISSN 2302-5808, was firstly published on March 24, 2013, in the context to commemorate the BLA (Bandung Lautan Api or Bandung a Sea of Flames)âs Day in Indonesia. Since issue of September 2013 to date, the SUSURGALUR journal has jointly been organized by the Lecturers of APB UBD (Academy of Brunei Studies, University of Brunei Darussalam) and the Lecturers of International and Historical Study Program FASS (Faculty of Arts and Social Sciences) UBD in Bandar Seri Begawan, Brunei Darussalam; and published by Minda Masagi Press as a publisher owned by ASPENSI (the Association of Indonesian Scholars of History Education) in Bandung, West Java, Indonesia. This journal is published twice a year i.e. every March and September.Â Bandung, Indonesia: March 24, 2016.Andi SUWIRTAChairperson of ASPENSI; and Senior Lecturer at the Department of History Education UPI (Indonesia University of Education) in Bandung, West Java, Indonesia.Â